2013
DOI: 10.1111/ijlh.12087
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a new panel of automated chemiluminescence assays for von Willebrand factor antigen and activity in the screening for von Willebrand disease

Abstract: This new VWD test panel has adequate laboratory characteristics and allows fully automated and simultaneous analysis of the VWF:Ag and VWF:RCo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 37 publications
5
36
0
Order By: Relevance
“…This patient had increased ristocetin-induced platelet agglutination at 0.3 mg mL À1 , and a type 2B mutation, and has been referred to in a previous publication [14]. Results of our comparison of VWF:RCo[Acu] with VWF:RCo [Agg] are in agreement with the findings reported by others [16,23], although Carbera et al [16] used a Behring Coagulation Timer rather than aggregometry for their reference VWF:RCo, and Verfaillie et al [23] did not assess samples from type 2 VWD. In contrast, Costa-Pinto et al [24], found higher results by AcuStar chemiluminescence assay compared with aggregometry, but also found low activity levels by AcuStar in 80 of their 81 patients with type 2 VWD, with only one type 2M patient detected by aggregometry and not by AcuStar.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This patient had increased ristocetin-induced platelet agglutination at 0.3 mg mL À1 , and a type 2B mutation, and has been referred to in a previous publication [14]. Results of our comparison of VWF:RCo[Acu] with VWF:RCo [Agg] are in agreement with the findings reported by others [16,23], although Carbera et al [16] used a Behring Coagulation Timer rather than aggregometry for their reference VWF:RCo, and Verfaillie et al [23] did not assess samples from type 2 VWD. In contrast, Costa-Pinto et al [24], found higher results by AcuStar chemiluminescence assay compared with aggregometry, but also found low activity levels by AcuStar in 80 of their 81 patients with type 2 VWD, with only one type 2M patient detected by aggregometry and not by AcuStar.…”
Section: Discussionsupporting
confidence: 90%
“… used a Behring Coagulation Timer rather than aggregometry for their reference VWF:RCo, and Verfaillie et al . did not assess samples from type 2 VWD. In contrast, Costa‐Pinto et al .…”
Section: Discussionmentioning
confidence: 99%
“…As expected, and also reported by others, all of the new assays (i.e. VWF:GPIbR by the HemosIL latex agglutination assay and the HemosIL AcuStar assay , the VWF:GPIbM Siemens assay and the VWF:Ab assay ) performed well and yielded results close to the old reference standard VWF:RCo. Although statistically significant and consistent in all participating laboratories, the slightly steeper regression lines for the VWF:Ab and VWF:GPIbM were clinically insignificant.…”
Section: Discussionsupporting
confidence: 89%
“…The ACL AcuStar™ analyzer (Instrumentation Laboratory Company, Bedford, MA, USA) is the first instrumentation introducing chemiluminescence technology to perform quantitative [HemosIL AcuStar VWF:Ag (VWF:Ag‐IL)] and qualitative immunoassays [HemosIL AcuStar VWF:RCo (VWF:RCo‐IL)] of VWF. Recent studies showed that this methods good performance and high sensitivity at low concentration of VWF makes it suitable for the diagnosis of VWD .…”
Section: Introductionmentioning
confidence: 99%